Penggunaan Model Pembelajaran Think Pair Share untuk Meningkatkan Hasil Belajar IPA Konsep Gaya pada Siswa Kelas IV SD Negeri Gomarmeti Kecamatan Aru Selatan Timur - Parsin, Topan; Pelamonia, J .; Pattinasarany, Theophanie (Universitas Pattimura, Program Studi Diluar Kampus Utama (Program Studi Pendidikan Guru Sekolah Dasar), 2022)
This study aims to determine the improvement of learning outcomes with the application of the think pair sharee (TPS) model. The research location was carried out in Gomarmeti State Elementary School, South East Aru District with the study subjects being grade IV students consisting of 25 students consisting of 15 men and 10 women. The purpose of this research is to increase knowledge in developing new ideas that will be used by teachers so as to improve student IPA learning outcomes on Style materials by applying think pair sharee learning models. In research using a type of class action research that is reflective by performing certain actions in order to improve and improve classroom learning practices more professionally. Furthermore, the results of this study are applied think pair sharee learning model in IPA learning can improve the learning outcomes of students in the fourth grade of Gomarmeti State Elementary School, South Aru Subdistrict...